Исследование технологических режимов термической обработки стали 60С2ХФА для улучшения механических характеристик рессорно-пружинных деталей (Вестник транспорта - Transport xabarnomasi, 2026)
The article considers the effects of the temperature of the cooling medium during heat treatment on the mechanical characteristics of spring steel 60Si2CrV. The dependences of hardness, tensile strength and elongation of steel on the temperature of the quenching medium are shown. It has been established that the optimal temperature range of the cooling medium is from 20 to 30 °C, which makes it possible to achieve high mechanical characteristics of the material. The results obtained can be useful for optimizing the heat treatment of cylindrical springs of freight wagons, ensuring their durability and reliability.